Gold metal waters: the Animas River and the Gold King Mine spill - Clark, Brad T., editor; McCormick, Pete, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
Inter- and transdisciplinary examination into the 2015 Gold King Mine spill in Silverton, Colorado, when three million gallons of subterranean mine water, carrying 880,000 pounds of heavy metals, spilled into a tributary of the Animas River. Illuminates the ongoing ecological, economic, political, social, and cultural significance of a regional event.--Provided by publisher.
Introduction: From gold medal to gold metal waters / Brad T. Clark -- A tale of two places: the upper and lower Animas River watersheds in Southwest Colorado / Brad T. Clark -- The Gold King Mine release: impacts on water quality and aquatic life / Scott W. Roberts -- A potent focusing event: the Gold King Mine spill and rapid policy development / Brad T. Clark -- From deep time to deep valleys: hydrology and ecology of the Animas River drainage / Cynthia Dott, Gary Gianniny, and David Gonzales -- Watershed consciousness: the Animas River and a sense of place / Pete McCormick -- Tourist Season / Lorraine L. Taylor and Keith D. Winchester -- Contaminated mines or minds: the psychological reaction to the Animas River spill / Brian L. Burke, Alane Brown, Betty Carter Dorr, and Megan C. Wrona -- Social impacts of the Gold King Mine spill to Animas-San Juan River watershed communities / Becky Clausen, Teresa Montoya, Karletta Chief, Steven Chischilly, Janene Yazzie, Jack Turner, Lisa Marie Jacobs, and Ashley Merchant -- The problems of litigating hardrock mining / Michael A. Dichio -- Divergent perspectives on AMD remediation in the upper Animas Watershed: pre- and post-spill policy preferences examined through the Advocacy Coalition framework / Brad T. Clark -- Afterword: we all live downstream / Andrew Gulliford.
Keywords: Acid mine drainage -- Colorado -- Gold King Mine (San Juan County); Abandoned mined lands reclamation -- Accidents -- Colorado -- Gold King Mine (San Juan County); Waste spills -- Colorado -- Gold King Mine (San Juan County); Water -- Pollution -- Animas River (Colo. and N.M.); Hard rock mines and mining -- Environmental aspects -- West (U.S.)